Technology and Special Educational Needs: Let’s Play “Doing Good Deeds!” - Soares, Filomena (2018)
“Doing Good Deeds!” is a game directed to children with special needs, in pre and elementary school age that aims to promote the development of social skills in different contexts. Structurally, this game has available a set of Avatars that players can choose to represent them. To adapt the game to each child, an administration module was developed, corresponding to the back office of the game, which allows the educator to create or change contexts, difficulty levels and sequences. This module includes also the visualization of the user performance, in particular the duration of each game, the number of attempts with and without success, allowing the educator to analyze the progress of each player.